Deviation of the Error Estimation for Second Order Fredholm-Volterra Integro Differential Equations. Issue 6 (1st November 2016) - Parvaz, Reza; Zarebnia, Mohammad; Saboor Bagherzadeh, Amir
Abstract: In this paper we study the deviation of the error estimation for the second order Fredholm-Volterra integro-differential equations. We prove that for m degree piecewise polynomial collocation method, our method provides O ( h m+1 ) as the order of the deviation of the error. Also numerical results in the final section are included to confirm the theoretical results.